Highly Stretchable, Adhesive, Biocompatible, and Antibacterial Hydrogel Dressings for Wound Healing - Yang, Zifeng; Huang, Rongkang; Zheng, Bingna; Guo, Wentai; Li, Chuangkun; He, Wenyi; Wei, Yingqi; Du, Yang; Wang, Huaiming; Wu, Dingcai; Wang, Hui (Advanced science, 2021)
Treatment of wounds in special areas is challenging due to inevitable movements and difficult fixation. Common cotton gauze suffers from incomplete joint surface coverage, confinement of joint movement, lack of antibacterial function, and frequent replacements. Hydrogels have been considered as good candidates for wound dressing because of their good flexibility and biocompatibility. Nevertheless, the adhesive, mechanical, and antibacterial properties of conventional hydrogels are not satisfactory. Herein, cationic polyelectrolyte brushes grafted from bacterial cellulose (BC) nanofibers are introduced into polydopamine/polyacrylamide hydrogels. The 1D polymer brushes have rigid BC backbones to enhance mechanical property of hydrogels, realizing high tensile strength (21–51 kPa), large tensile strain (899–1047%), and ideal compressive property. Positively charged quaternary ammonium groups of tethered polymer brushes provide long‐lasting antibacterial property to hydrogels and promote crawling and proliferation of negatively charged epidermis cells. Moreover, the hydrogels are rich in catechol groups and capable of adhering to various surfaces, meeting adhesive demand of large movement for special areas. With the above merits, the hydrogels demonstrate less inflammatory response and faster healing speed for in vivo wound healing on rats. Therefore, the multifunctional hydrogels show stable covering, little displacement, long‐lasting antibacteria, and fast wound healing, demonstrating promise in wound dressing. A new class of highly stretchable, adhesive, biocompatible, and antibacterial hydrogel dressing is designed and prepared by synergizing biocompatible polyacrylamide hydrogel scaffold, biological adhesive polydopamine, and antibacterial polymer brush grafted from bacterial cellulose nanofibers.